Marine bioactive peptides as potential therapeutic agents for wound healing – a review - Kai Zheng; Ziwei Yang; Te Ba (Annals of Medicine, 2025)
Context Skin wounds resulting from dermatological diseases and other specific causes present significant challenges in health care. These wounds can lead to infections, chronic conditions, long-term complications and even mortality. Consequently, developing highly effective and viable therapies for wound healing is important. Marine bioactive peptides are increasingly being utilized because of their favourable biological properties, which include anti-inflammatory, antioxidant, antimicrobial, antiageing, antitumour and antihypertensive effects. These peptides offer several advantages, including high efficacy, excellent safety, clear target specificity and low allergenicity. Notably, scientific evidence has demonstrated that marine bioactive peptides promote skin injures repair and has underscored their substantial potential in wound healing.Objective Our objective is to provide molecular insights that may facilitate the development of innovative therapeutic agents aimed at improving wound healing and skin repair.Materials & methods This review synthesizes information from major databases, including ScienceDirect, Google Scholar, Scopus, PubMed and Springer Link. Publications were selected without date restrictions and used terms such as skin injures, wound healing, marine bioactive peptides, antimicrobial, ceRNA. Articles related to agriculture, ecology, or synthetic work or those published in languages other than English were excluded.Results and conclusions In this review, we integrated and examined the current understanding of wound care. Additionally, we analysed the underlying molecular mechanisms involved to elucidate the characteristics of marine bioactive peptides.